Hydrogen gas and biochar production from kitchen food waste through dark fermentation and pyrolysis - Pradhan, Snigdhendubala; Yuzer, Burak; Bicer, Yusuf; McKay, Gordon; Al-Ansari, Tareq (Frontiers in Chemical Engineering, 2024)
Transportation and consumption of kitchen food waste contributes a major role in greenhouse gases (GHGs) emission in global warming. To reduce this risk, recycling of food waste to energy production and agriculture byproduct for nutrient management is important. Dark fermentation process is one of the most suitable nutrient recovery techniques to generate hydrogen (H2) gas and serves as a clean energy carrier concerning a sustainable environment. Out of many vegetables and fruits, potatoes (Solanum tuberosum L.) and watermelon (Citrullus lanatus) are two important market demanding vegetable and fruit worldwide. In each year, almost 8000 kilotons of potato peels are generated with a GHGs emissions of 5 million tonnes of CO2 equivalent. A watermelon consists of more than 90% of the rind which is consider as a waste and discarded. Considering these two wastes, a short scale preliminary research was conducted to produce H2 gas from potato peels, watermelon rinds, and a mixture of peels and rinds by dark fermentation process. After the volume analysis of the produced H2 gas, the remaining resides were used to produce biochar. A higher volume of 149 mL H2 gas was achieved from peels followed by 140 mL and 135 mL of H2 gas from rinds and mixture of peels and rinds respectively with a biomass pH of 4.7 to 5.6 and volatile solid (VS) of 77 to 88%. The biochar produced from all the sample types was alkaline in nature with a pH of 7.88 ±0.33, electrical conductivity of 0.38 ±0.03 mS/cm, zeta potential of -25.12 ±0.32 mV and nutrient rich that could be beneficial for soil quality improvement and plant growth. However, the outcomes of this small cycle of analysis required additional analytical outcomes with field application that targets the future scope of research on sustainable H2 production and agriculture application.